Localization of 18S ribosomal genes in suckermouth armoured catfishes Loricariidae (Teleostei, Siluriformes) with discussion on the Ag-NOR evolution - Alves, Anderson Luis [UNESP]; de Borba, Rafael Splendore [UNESP]; Pozzobon, Allan Pierre Bonetti [UNESP]; Oliveira, Claudio [UNESP]; Nirchio, Mauro; Granado, Angel; Foresti, Fausto [UNESP] (Pensoft Publishers, 2012)
The family Loricariidae with about 690 species divided into six subfamilies, is one of the world's largest fish families. Cytogenetic studies conducted in the family showed that among 90 species analyzed the diploid number ranges from 2n=38 in Ancistrus sp. to 2n=96 in Hemipsilichthys gobio Luetken, 1874. In the present study, fluorescence in situ hybridization (FISH) was employed to determine the chromosomal localization of the 18S rDNA gene in four suckermouth armouredcatfishes: Kronichthys lacerta (Nichols, 1919), Pareiorhaphis splendens (Bizerril, 1995), Liposarcus multiradiatus (Hancock, 1828) and Hypostomus prope plecostomus (Linnaeus, 1758). All species analyzed showed one chromosome pair with 18S rDNA sequences, as observed in the previous Ag-NORs analyses. The presence of size and numerical polymorphism was observed and discussed, with proposing a hypothesis of the Ag-NOR evolution in Loricariidae. © Anderson Luis Alves et al.
Keywords: Fish cytogenetics; Fluorescent in situ hybridization; Loricariidae